1994
DOI: 10.1111/j.1398-9995.1994.tb02096.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of allergic symptoms in children with those in their parents

Abstract: This study investigated the association of asthma, allergic rhinitis, and eczema in United Arab Emirates (UAE) schoolchildren with allergic conditions in their parents. A cross-sectional, population-based study among schoolchildren aged 6-14 years was conducted in Al-Ain City, UAE. The field survey was conducted from October 1992 to May 1993. A questionnaire was distributed to 850 UAE government school students from representative, randomly selected schools with a majority of UAE nationals. The student and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…In this study, maternal asthma was consistently associated with wheezing and recurrent wheezing in the offspring, a finding already observed in different populations and considered an important risk factor for asthma in children before 5 years [58-61]. The mechanisms of this "maternal effect" and why it is more evident during early childhood are unknown.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, maternal asthma was consistently associated with wheezing and recurrent wheezing in the offspring, a finding already observed in different populations and considered an important risk factor for asthma in children before 5 years [58-61]. The mechanisms of this "maternal effect" and why it is more evident during early childhood are unknown.…”
Section: Discussionmentioning
confidence: 54%
“…22 However, children's asthma above 5 years of age had a similar influence to fathers' and mothers' asthma 22 ; the same observation was seen in studies of older children and young adults. 23 24 We have no clear explanation for the observed negative association between paternal and their offspring's asthma. Under-diagnosis of asthma among fathers is possible, which would underestimate an association between asthma in fathers and offspring.…”
Section: Discussionmentioning
confidence: 94%
“…15,16 In a previous cross-sectional analysis of 217 siblings of the index children from this at-risk birth cohort, Litonjua et al 11 showed that the risk of childhood asthma before the age of 5 years was strongly associated with a maternal history of asthma. However, in agreement with our findings, maternal and paternal asthma were associated with similar risks among children older than 5 years of age.…”
Section: Discussionmentioning
confidence: 97%